2023
DOI: 10.1111/bju.15959
|View full text |Cite
|
Sign up to set email alerts
|

Machine‐learning approach for prediction of pT3a upstaging and outcomes of localized renal cell carcinoma (UroCCR‐15)

Abstract: To assess the impact of pathological upstaging from clinically localized to locally advanced pT3a on survival in patients with renal cell carcinoma (RCC), as well as the oncological safety of various surgical approaches in this setting, and to develop a machine-learning-based, contemporary, clinically relevant model for individual preoperative prediction of pT3a upstaging. Materials and MethodsClinical data from patients treated with either partial nephrectomy (PN) or radical nephrectomy (RN) for cT1/cT2a RCC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
(57 reference statements)
0
5
0
1
Order By: Relevance
“…However, despite some promising results, recent studies show that the benefits of ML are not ubiquitous, especially when deployed on imperfect and non-granular datasets [2].In this issue of the BJUI, Boulenger de Hauteclocque employ data from the French multi-institutional kidney cancer database UroCCR (ClinicalTrials.gov Identifier: NCT03293563), to investigate the ability of seven ML algorithms to predict pT3a upstaging in a cohort of patients who underwent surgery for cT1/cT2a RCC. Using supervised ML algorithms, they reported a prediction accuracy (measured by the area under the receiver-operating curve) of 0.77 for their best model [3]. While the results are intriguing, the design of the study raises questions that should be considered by clinicians when interpreting the results.…”
mentioning
confidence: 99%
“…However, despite some promising results, recent studies show that the benefits of ML are not ubiquitous, especially when deployed on imperfect and non-granular datasets [2].In this issue of the BJUI, Boulenger de Hauteclocque employ data from the French multi-institutional kidney cancer database UroCCR (ClinicalTrials.gov Identifier: NCT03293563), to investigate the ability of seven ML algorithms to predict pT3a upstaging in a cohort of patients who underwent surgery for cT1/cT2a RCC. Using supervised ML algorithms, they reported a prediction accuracy (measured by the area under the receiver-operating curve) of 0.77 for their best model [3]. While the results are intriguing, the design of the study raises questions that should be considered by clinicians when interpreting the results.…”
mentioning
confidence: 99%
“…Boulenger de Hauteclocque et al. [1] tested different ML algorithms to predict upstaging to pathological tumour stage pT3a in patients undergoing surgery for clinical tumour stage cT1/cT2a renal cell carcinoma. The best prediction model achieved an area under the receiver‐operating characteristic curve of 0.77.…”
Section: Checklist Usementioning
confidence: 99%
“…Astrid Boulenger de Hauteclocque 1 , Lo€ ıc Ferrer 2 , Ga€ elle Margue 1 , Guillaume Etchepare 2 , Thierry Colin 2 and Jean-Christophe Bernhard 1…”
Section: Fundingunclassified
“…A plethora of studies has focused on the key determinants of postoperative functional outcomes [1]. If renal ischaemia has historically been one of the most important drivers of early functional impairment, growing evidence has suggested that type and duration of ischaemia have far less long-term influence than other factors [2].…”
Section: Fundingmentioning
confidence: 99%
See 1 more Smart Citation